Implementation of Process Oriented Guided Inquiry Learning Model Learning (Pogil) on Understanding of Science Concepts, Skills Science Process and Student's Critical Thinking Ability - Samosir, Beslon (International Journal of Multidisciplinary: Applied Business and Education Research, 2022)
The purpose of this study was to determine the effect of the Audi Video Tenik Class XI Student Learning model at SMK Negeri 2 Pematangsiantar who had not carried out scientific inquiry in an effort to grow the ability to think, work, and behave scientifically. This study is a quasi-experimental design study with a nonequivalent control group. Sampling technique with a simple random sample. Hypothesis testing using Manova analysis and t test. The results showed that (1) there was an effect of the POGIL learning model on understanding science concepts, (2) there was an effect of the POGIL learning model on science process skills, (3) there was an effect of the POGIL learning model on critical thinking skills, and (4) there was a significant effect. significant application of the POGIL learning model simultaneously to understanding science concepts, science process skills, and critical thinking skills.